The LUCINDA trial: Leuprolide + cholinesterase inhibition to reduce neurologic decline in Alzheimer's: Human/Human trials: Other. (7th December 2020) - Butler, Tracy; Atwood, Craig S.; Galvin, James E.; Maloney, Thomas; Glodzik, Lidia; de Leon, Mony J.; Goldberg, Judith D.
Abstract: Background: Leuprolide Acetate has been used for decades to treat hormone‐sensitive conditions such as prostate cancer and endometriosis. In animal models of AD, leuprolide preserves cognition and decreases amyloid deposition and tau phosphorylation by decreasing levels of Luteinizing Hormone. A subgroup analysis of a prior human trial (Bowen, 2016) showed that leuprolide benefited cognition and function in women who were also taking donepezil. Here we describe an ongoing clinical trial of leuprolide to confirm and extend these results. Method: A three‐site, double‐blind, randomized trial of Leuprolide Acetate (22.5 mg/12 weeks) compared with placebo to evaluate the changes over 48 weeks in cognition, function, brain MRI measures (volume, hippocampal blood flow) and blood biomarkers of inflammation in women (n=150) with mild‐moderate AD who are also taking a stable dose of donepezil. This trial is enrolling at three US sites: Weill Cornell in NYC, University of Miami in Southern FL and University of Wisconsin, Madison. Result: Results are expected in 2025. Conclusion: By re‐purposing an existing medication, in combination with a current AD treatment, we will be able to build upon extensive previous research and development efforts, reducing the time frame and costs of making this promising therapy available to patients with AD. Re‐purposing an existing drug likely represents the only realistic option for meeting the HHS goal to "Prevent and Effectively Treat Alzheimer's Disease and Related Dementias by 2025."